Pencegahan Tindakan Kekerasan Dalam Pendidikan Pesantren - Adi Gunawan; Ach. Rifai; Gatot Subroto; Adriana Pakendek; Win Yuli Wardani; Sapto Wahyono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Pesantren is one of the educational institutions that is connoted with Islamic education which is allocated in a certain place with the aim that education will be more effective. Pesantren education is led by a Kyai who is then delegated to the pesantren management consisting of teachers and senior students. Starting from the many negative news in the electronic media of violence in pesantren committed by senior students on their juniors which resulted in victims being disabled, injured and even died, of course this event is very unfortunate and very undesirable for all parties. Therefore, to prevent these actions from occurring in the Al-Amien Prenduan pesantren environment, it is necessary to carry out legal counseling for senior santri which aims to prevent acts of violence in enforcing pesantren discipline from occurring in the future.